EFFECT OF WORK ENVIRONMENT AND COMPENSATION TO EMPLOYEE PERFORMANCE - Fajrianto, Nugroho; Nurdiansyah Putra, Fajar; Faris Abdul Majid, Raden; Yulianti Kurniawan, Irma; Tarmidi, Didi (International Journal of Psychosocial Rehabilitation, 2020)
This research revealed that there is a gap between the existence of a good work environment and compensation that has been done but the employee's performance can’t get the specified target. This research aims to find out whether the work environment and compensation affect the performance of employees of CV Nugroho Hadi Putra. The factors tested in this research are the work environment and compensation as the independent variable, while employee performance as the dependent variable. This research used descriptive method, with data collection techniques through by observation and questionnaire distribution. The population of this research were employees of CV Nugroho Hadi Putra with a sample of 100 respondents. Data analysis using multiple linear regression analysis at significant level of 5 percent. The programs used are SPSS 25 and Lisrel 8.80. The results of this research showed two independent variables, that is work environment and compensation are not significantly influence of employee performance.